Growth and yield of elite genotypes of chilli (Capsicum annuum L.) in diverse agroclimatic zones of Punjab - S K Jindal, D S Cheema, M S Dhaliwal, N Garg, (Journal of Spices and Aromatic Crops, 2015)
Eleven elite genotypes of chilli along with one check (Punjab Surkh) were evaluated at two diverse locations of Punjab, India. The G × E interaction was significant for red ripe fruit yield, fruit width and fruit weight and genotype Acc-33-1 was the most stable across locations. The pooled analysis showed that the genotype, SD 463 had the maximum red ripe fruit yield (0.586 kg plant-1) and fruit weight (4.1 g); Mehma Sarja had the highest plant height (93.5 cm) and fruit width (13.4 mm); Selection 7 exhibited the lowest plant height (37.6 cm) and fruit width (7.0 mm); PC-6-1 had the longest fruits (8.6 cm); DCL 524 possessed maximum number of seeds fruit-1 (43.5); Selection 36-1 produced the maximum seed weight (0.211 g fruit-1). The low broad sense heritability (h2) for number of seeds fruit-1 and dried seed weight fruit-1 revealed that these traits were highly influenced by environment. High heritability coupled with high genetic advance for red ripe fruit yield, fruit weight, plant height, fruit length and fruit width indicated the important role played by additive gene effects.